2022
DOI: 10.21037/atm-22-1946
|View full text |Cite
|
Sign up to set email alerts
|

GFAT1 is highly expressed in cancer stem cells of pancreatic cancer

Abstract: Background: Cancer stem cells (CSCs) play pivotal roles in the growth, invasion, metastasis, and chemoresistance of pancreatic cancer (PC). The current characterization of CSCs in PC is not complete.Glutamine-fructose-6-phosphate transaminase 1 (GFAT1) is a key enzyme that regulates the hexosamine pathway (HP), in which it not only controls glucose influx but also catalyzes the reaction to form glucosamine 6-phosphate. Recently, it was reported that GFAT1 is highly expressed in PC. However, the relevance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…Additionally, the in vitro expression of GFAT1 was linked to gemcitabine resistance. 33 In patients with PDAC, stem cell markers CD44, CD133, and ALDH1 were present at higher levels in samples from individuals who underwent neoadjuvant chemoradiotherapy compared with those who did not receive this treatment. [42][43][44][45] This suggests that cells expressing these markers are more resistant to the chemoradiotherapy.…”
Section: Pancreatic Cancer Stem Cells Markers and Its Role In The Pda...mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the in vitro expression of GFAT1 was linked to gemcitabine resistance. 33 In patients with PDAC, stem cell markers CD44, CD133, and ALDH1 were present at higher levels in samples from individuals who underwent neoadjuvant chemoradiotherapy compared with those who did not receive this treatment. [42][43][44][45] This suggests that cells expressing these markers are more resistant to the chemoradiotherapy.…”
Section: Pancreatic Cancer Stem Cells Markers and Its Role In The Pda...mentioning
confidence: 99%
“…In further studies, additional markers for PCSCs have been identified, such as cathepsin B, glutamine-fructose-6-phosphate transaminase 1 (GFAT), doublecortin, acetylated α-tubulin, and aldehyde dehydrogenase 1 (ALDH1) 30–33 . The fact that several markers were found, but not always coexpressed, suggests that pancreatic adenocarcinoma may contain multiple populations of CSCs (Fig.…”
Section: Cancerous Stem Cells and Pdac Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing GFAT1 reduces O-GlcNAc levels and inhibits PC cell growth ( Jia et al, 2020 ; Yamamoto et al, 2022 ). Both CD133+ or CD44 + PC stem cells have higher GFAT1 levels and are more resistant to GEM-induced apoptosis than cells with corresponding marker loss ( Wang Z. et al, 2022 ). Stomatin like protein 2 is a mitochondrial-associated protein upregulated after GEM stimulation.…”
Section: Alterations In Glucose Metabolismmentioning
confidence: 99%
“…This increase in HBP activity and UDP-GlcNAc level could be a result of an increased influx of metabolites such as glucose and glutamine into the HBP pathway ( 20 ). However, other reports also suggested that the expression of key enzymes of the HBP is elevated in cancer, which might result in the elevated activity of the HBP and potentially contribute to drive tumor growth ( 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ).…”
Section: The Hexosamine Biosynthetic Pathwaymentioning
confidence: 99%